Pelaksanaan Program Zero Street Crime Sistem Dalam Menanggulangi Kejahatan Jalanan Di Wilayah Hukum Polrestabes Makassar - Ahmad Akbar Maulana; Hamsir (Law Department, Universitas Islam Negeri Alauddin Makassar, 2022)
The main problem of this research is how the efforts of actions related to criminal offenses, especially in street crimes,”have been rampant so far, in this case there are many different types of actions such as curas, spout, curanmor and so on.“So with the existence of regulations that have been made in the Criminal Code”as well as the implementation of a program that has been implemented in efforts to tackle“street crimes that the Makassar City Police Resort has carried out to date.”With a research approach using statutory research as well as from the implementation of related programs, using an empirical juridical approach or facts that occur in practice in the field and also a sociological approach.“Sources of data used are primary data and secondary data, as well as methods in data collection are the result of observations,”interviews and documentation.“Meanwhile, data processing and analyzing was carried out in two stages, namely 1) data processing techniques in the form of data classification, data reduction and data editing. 2) data analysis techniques.”The results of the research obtained are:”1) The implementation of the Zero Street Crime program uses three functions, namely preemptive, preventive and responsive functions to suppress the number of street crimes in the Makassar area and try to increase public trust in the Police and also create a social security situation free from crime disturbance especially in street crime. 2)“The obstacles faced by the Makassar Police are the insufficient number of personnel that are not proportional to the area of ​​the city of Makassar,” the absence of a forum such as a rehabilitation institution that can provide good guidance for “ANJAL (Street Children), PMKS (People with Social Welfare Problems) , as well as low verdicts or sentences that gave rise to many recidivists.